A Cross-Cultural Pragmatics Study of Request Strategies and Politeness in Javanese and Sundanese - Chintawidy, Permas Adinda; Sartini, Ni Wayan (Journal of Pragmatics Research, 2022)
This study aims to examine and compare request strategies and politeness of two groups of native speakers from two different ethnic groups in Indonesia, i.e., Javanese and Sundanese. The data were collected by using Discourse Completion Task (DCT) with 60 participants from 30 Javanese (East Java) and 30 Sundanese (West Java) speakers. The data were analyzed by using the classification of request strategies by Blum-Kulka et al., 1989) and social contexts in terms of social power, social distance, and degree of imposition by Brown and Levinson (1987) to reveal the levels of directness and politeness of request employed by each group of speakers. The result of this study indicates that Direct Strategy in the form of mood derivable and Conventionally Indirect Strategy in the form of query preparatory are two request strategies that are mainly employed by both Javanese and Sundanese speakers. In particular, Javanese speakers employ a more Direct Strategy than Sundanese speakers. However, the patterns of request strategies employed by Javanese and Sundanese speakers in most social contexts are similar. In addition, both groups of speakers can also adapt to the situations and employ appropriate requests to the hearer. Therefore, politeness and appropriateness in requests employed by each group of speakers in their DCT responses can reflect the local wisdom of each culture.Keywords: requests; social contexts; politeness; Javanese; Sundanese